Miskonsepsi Materi IPA Kelas 5 Perpindahan Kalor di Sekitar Kita pada SDN 1 Kancilan - Sukamto Sukamto; Sumarno Sumarno; Joko Siswanto (Fakultas Keguruan dan Ilmu Pendidikan - Universitas Gresik, 2022)
Learning occurs interaction between teachers and students and learning resources in a learning environment. Learning activities are a process of assistance provided by educators/teachers to students so that the process of acquiring knowledge, mastering skills, forming attitudes and self-confidence can occur in students. In the learning process students come with the provision of knowledge and skills. The initial abilities possessed by students are sometimes not in accordance with the concepts contained in the subject matter. The science subject matter is closely related to the natural environment which is very broadly related to everyday human life. Often found misunderstanding of the concepts of Natural Sciences. If students' misunderstandings are allowed to occur, there will be continuous and continuous misconceptions that will affect the quality of students. The purpose of this study was to find out how the initial cognitive ability and its relation to the misconceptions of science learning about heat transfer in class V students. This research method used a quantitative descriptive approach with the object of research being class V students at SDN 1 Kancilan Kembang Jepara. The instrument used in this study was the There Tier-Test which was used to determine initial abilities and identify misconceptions that occurred in fifth grade students. Data analysis in this study was carried out using percentage techniques. The results showed that in general the fifth grade students at SDN 1 Kancilan already had 43% of the initial cognitive knowledge to understand the concept of heat transfer related to daily life events, while those who experienced misconceptions about heat transfer material were 28%. Experiencing misconceptions (False Positive) by 19%, and those who experience misconceptions (False Negative) by 10%. As the beginning of the meeting, the provisions brought by students regarding heat transfer material were mastery of the concept of the Low category, the level of misconceptions was in the Low category, those who experienced misconceptions (False Positive) were in the Low category and those who experienced misconceptions (False Negative) were in the low category. Thus in learning, students already have initial knowledge but still experience misconceptions about concepts in science subjects regarding heat transfer in events in everyday life, so innovation, strategies, methods are needed in learning in class V students on the concept heat transfer material so that misconceptions do not occur continuously and continuously.